Examining the influence of innovative leadership on the innovative work environment - Barroga, Jean Rachel; Fredolin P. Julian; Abun, Damianus (Divine Word International Journal of Management and Humanities (DWIJMH) (ISSN: 2980-4817), 2023)
The study intended to examine the effect of innovative leadership on the innovative work environment of the Divine Word College of Laoag. To carry out the study, the literature was reviewed and the study used the descriptive research design. The questionnaires were used to gather the data and the respondents were the employees of the Divine Word College of Laoag. The study found that the innovative leadership of administrators and the innovative work environment of the Divine Word College of Laoag is considered high. However, the correlation test found that there is no correlation between innovative leadership and an innovative work environment. Thus, the hypothesis is rejected. It just means that innovative leadership has nothing to do with the innovative work environment. The innovative work environment can be caused by other factors not included in the current study.